Effect of Various Superplasticizers on the Textural Properties of Silica Fume Pozzolanic Cements - Nasr-Allah M. Deraz; Mohamed Heikal; Hamdy El-Didamony (Adsorption Science & Technology)
The influence of different superplasticizers on the hydration and textural characteristics of hardened pozzolanic cement pastes was evaluated. Thus, the BET surface areas and pore structures of hardened cement pastes containing different amounts of silica fume and/or various superplasticizers were determined via nitrogen adsorption isotherms measured at −196°C. Three types of superplasticizers were used in this study, viz. naphthalene formaldehyde sulphonate (NFS), sodium gluconate (SG) and their mixtures (NFS + SG). The various phase compositions and microstructures were assessed by X-ray diffraction (XRD) and scanning electron microscope (SEM) studies. The results revealed that the specific surface area (S BET ) of the hardened cement pastes decreased as the amount of silica fume increased and also on addition of superplasticizer. The decrease in surface area was more pronounced in the presence of 30 wt% silica fume as well as with superplasticizers. Thus, the maximum decrease in the S BET value due to the addition of 4% NFS superplasticizer attained values in the range 46–68%. In addition, increasing the curing time from 3 d up to 180 d decreased the surface area of the pure and superplasticized cement pastes. The decrease in S BET for the various cement pastes could be attributed to the pozzolanic activity of the silica fume with a subsequent increase in the amount of hydration products within the pore system.